2024
DOI: 10.3389/fimmu.2023.1306534
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of NK cells and radiotherapy in the treatment of solid tumors

Wang Zheng,
Sunkai Ling,
Yuandong Cao
et al.

Abstract: Natural killer (NK) cells are innate lymphocytes possessing potent tumor surveillance and elimination activity. Increasing attention is being focused on the role of NK cells in integral antitumor strategies (especially immunotherapy). Of note, therapeutic efficacy is considerable dependent on two parameters: the infiltration and cytotoxicity of NK cells in tumor microenvironment (TME), both of which are impaired by several obstacles (e.g., chemokines, hypoxia). Strategies to overcome such barriers are needed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 152 publications
0
1
0
Order By: Relevance
“…Radiation therapy plays an important role in the treatment of almost all solid cancers, with wide clinical application and satisfactory results, but there are still some obstacles limiting the efficacy of treatment, such as chemotherapy resistance. An example of the combination of radiation therapy with exosomes of natural killer cell origin is that they contain molecules that activate radio sensitization pathways [ 65 ]. Zhu et al showed that exosomes of natural killer cell origin can enter tumor cells and improve the efficacy of antitumor radiation therapy, such as in melanoma [ 18 ].…”
Section: Synergies Of Engineered Natural Killer Cell-derived Exosomes...mentioning
confidence: 99%
“…Radiation therapy plays an important role in the treatment of almost all solid cancers, with wide clinical application and satisfactory results, but there are still some obstacles limiting the efficacy of treatment, such as chemotherapy resistance. An example of the combination of radiation therapy with exosomes of natural killer cell origin is that they contain molecules that activate radio sensitization pathways [ 65 ]. Zhu et al showed that exosomes of natural killer cell origin can enter tumor cells and improve the efficacy of antitumor radiation therapy, such as in melanoma [ 18 ].…”
Section: Synergies Of Engineered Natural Killer Cell-derived Exosomes...mentioning
confidence: 99%